2015
DOI: 10.1002/sca.21242
|View full text |Cite
|
Sign up to set email alerts
|

Microshear bond strength of preheated silorane‐ and methacrylate‐based composite resins to dentin

Abstract: Summary:The aim of this study was to investigate the effect of preheating on microshear bond strength (MSBS) of silorane and methacrylate-based composite resins to human dentin. The teeth were randomly divided into three main groups: (1) composite resins were heated upto 68˚C; (2) cooled to 4˚C; and (3) control [room temperature (RT)]. Each group was then randomly subdivided into four subgroups according to adhesive system used [Solobond M (Voco), All Bond SE (Bisco), Clearfil SE Bond (CSE) (Kuraray), Silorane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
9
0
2
Order By: Relevance
“…Similar to the present study, Demirbuga et al found that there were significant differences between the bond strengths of preheated and nonheated composites to dentin surfaces. 23 Goulart et al evaluated the microtensile bond strength and adhesive interfaces of indirect restorations luted with preheated composite resin. 12 One resin cement (RelyX ARC) and two composite resins (Venus and Z250 XT) were used in their study, and the materials were preheated to 64°C.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the present study, Demirbuga et al found that there were significant differences between the bond strengths of preheated and nonheated composites to dentin surfaces. 23 Goulart et al evaluated the microtensile bond strength and adhesive interfaces of indirect restorations luted with preheated composite resin. 12 One resin cement (RelyX ARC) and two composite resins (Venus and Z250 XT) were used in their study, and the materials were preheated to 64°C.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the third tested hypothesis that the filler content and the pre-heating would have influence on the bond strength to the enamel was rejected. However, other studies did find differences in the bond strength between pre-heated and non-heated conventional composites and dentin (19). In this study, it was chosen to use enamel as a substrate because it is more homogeneous than dentin and also because it allows to test the bond strength after the passage of light through the ceramic veneer and resin material.…”
Section: Discussionmentioning
confidence: 99%
“…Dessa forma, o pré-aquecimento de resina composta antes da fotopolimerização teve muitas vantagens potenciais, como o aumento o grau de conversão de monômero e aumento da dureza da superfície. Além disso, estudos anteriores mostraram que o procedimento de pré-aquecimento aumentou o fluxo e melhorou a adaptação da resina nas paredes da cavidade e, portanto, microinfiltração potencialmente reduzida (Demirbuga et al, 2016). Todavia, Salgado et al (2010), enfatizou que em condições isotérmicas o pré-aquecimento de composto (60Cº) é capaz de aumentar a conversão de monômero, conforme a mobilidade molecular é aumentada e a frequência de colisão de espécies reativas é aumentada, tendo assim melhores propriedades mecânicas.…”
Section: Discussionunclassified